2020
DOI: 10.1109/access.2020.3012770
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Sideslip Angle Estimation for a Heavy-Duty Vehicle via Extended Kalman Filter Using a Rational Tyre Model

Abstract: Vehicle sideslip angle is a key state for lateral vehicle dynamics, but measuring it is expensive and unpractical. Still, knowledge of this state would be really valuable for vehicle safety systems aimed at enhancing vehicle safety, to help to reduce worldwide fatal car accidents. This has motivated the research community to investigate techniques to estimate vehicle sideslip angle, which is still a challenging problem. One of the major issues is the need for accurate tyre model parameters, which are difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The steady-state or transient conditions are discriminated via a fuzzy-logic procedure. Furthermore, the bicycle model can also be coupled with nonlinear tire models, as in [ 16 ], where the authors attempt to estimate the sideslip angle of a heavy-duty vehicle by using a rational tire model and an EKF as the estimator. The study showed good estimation performance, but at the cost of an overparametrized and complex model.…”
Section: Introductionmentioning
confidence: 99%
“…The steady-state or transient conditions are discriminated via a fuzzy-logic procedure. Furthermore, the bicycle model can also be coupled with nonlinear tire models, as in [ 16 ], where the authors attempt to estimate the sideslip angle of a heavy-duty vehicle by using a rational tire model and an EKF as the estimator. The study showed good estimation performance, but at the cost of an overparametrized and complex model.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, [26] introduces cornering stiffnesses directly in the state vector, hence obtaining their real-time estimation. [27] applies the same idea to the parameters of the Rational tire model.…”
Section: Introductionmentioning
confidence: 99%
“…Consolidated fuzzy estimation algorithms are used on this purpose by ABS control systems [49,50]. The vehicle sideslip angle is estimated through algorithms such as in [51,52], again based on standard automotive sensors like those reported in Tables 2, 3 and 4.…”
Section: Measurements and Sensorsmentioning
confidence: 99%